Spatial and temporal evolution of carbon stocks in Yulin City under changing environments - Guikai Sun; Yadong Li; Rui Huang; Chongxun Mo (Scientific Reports)
Abstract Land use changes directly or indirectly affect the regional carbon balance. Investigating the spatial and temporal evolution of regional carbon stock and the contribution of land use driving factors is crucial for understanding the formation mechanisms of ecosystem carbon cycles and carbon budget balance.In this study, the researchers selected the model simulation method after comparing various carbon stock estimation methods. This paper uses the InVEST model to calculate the carbon stock of Yulin City from 2000 to 2020. It then applies the PLUS model to predict the land use of Yulin City under different scenarios in 2030 and forecasts the future carbon stock, providing a theoretical basis for the city’s future development planning. The main findings of this study are as follows: (1) The land use transfer in Yulin City, Guangxi, from 2000 to 2020, is mainly among forest land, arable land, and construction land. The net transfer out of cultivated land is 476.9982 km2, and the net transfer in forest land and construction land is 245.5803 km2 and 231.0048 km2, respectively. (2) The study area’s carbon stock distribution closely follows the regional elevation pattern. The high-carbon stock areas concentrate in the mountainous and hilly regions of Yulin City at higher elevations. Medium-value areas lie in the study area’s relatively flat central and southern parts. In contrast, low-value areas are located in the reservoirs and rivers within Yulin City. (3) Compared with 2000, the carbon stock of the regional ecosystem in 2020 increased by 2.16 × 106 t. Compared with 2020, the carbon stock of the regional ecosystem in 2030 increased under NDS and EPS by 0.3214 × 106 t and 0.3286 × 106 t, respectively, and decreased under CPS by 2.1524 × 106 t. Overall, the carbon stock in 2030 increased by 0.3214 × 106 t compared with 2020 and decreased by 2.1524 × 106 t compared with 2020. Overall, the carbon stock in 2030 is expected to increase compared to 2020, but the growth rate is declining. The trend of increasing carbon stock in Yulin City is likely to continue decreasing in the future, and may even show a reduction.